(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Titanium dioxide Nano particles have been used as a core material for the design of low-cost sustainable power source, the dye sensitized cell. In this work, dye sensitized cell was investigated to be used as a self-powered ultra violet light detector in a data acquisition system. To enhance the detector robustness, the device was sealed using cross-linked photo resist to isolate it from the environmental effects. The detector was tested in air as well as in water to proof its characteristics in various environmental conditions. High responsivity and fast response were achieved for both discrete and continuous ultraviolet (UV) illuminations. To prove the self-powered property of the sensor, it was interfaced to a microcontroller. Our experimental results confirmed that there is no need of intermediate electronics such as signal conditioning in the interfacing circuit. Furthermore, the detector observed obvious selectivity for different light colors. This characteristic makes it candidate for the development of color sensors.